The influence of sintering process and atmosphere on the non-ohmic properties of SnO2 based varistor - Leite, E. R.; Nascimento, A. M.; Bueno, Paulo Roberto [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Kluwer Academic Publ, 1999)
The non-ohmic properties of the 98.95% SnO2 + 1.0 CoO + 0.05 Nb2O5 (all in mole%) system, as well as the influence of sintering temperature and atmosphere on these properties, were characterized in this study. The maximum non-linear coefficient (alpha = 32) was obtained for a sintering temperature of 1300 degrees C in an oxygen atmosphere and this maximum is associated with the presence of O in SnO2 grain boundaries, as interface defects. Experimental results also indicate thermionic-type conduction mechanisms, which are associated with the potential barrier of Schottky or Poole-Frenkel types.